The relationship between inclusive leadership and teachers' perceptions of organizational trust: A cross-sectional survey in Türkiye - Murat Polat; Kübra Turhaner (Journal of Pedagogical Research, 2024)
Significant scholarly attention has been devoted to investigating the relationship between school leadership and trust, with recent emphasis shifting towards inclusive leadership. This study specifically explores the connection between inclusive leadership and the level of trust within educational organizations. The main objective is to evaluate how administrators' Inclusive Leadership behaviors in public schools impact teachers' perceptions of Organizational Trust. To achieve this, the researchers engaged with teachers from various public schools in a city located in East Anatolia, Türkiye, employing a cross-sectional survey approach. A total of 273 teachers from diverse educational levels, including pre-school, primary, secondary, and upper-secondary school, participated in the study, with a gender distribution of 143 females and 130 males. Data were collected through the Inclusive Leadership scale and Organizational Trust scale, and data analysis utilized regression analysis techniques. The findings reveal a robust and positive correlation between inclusive leadership practices in educational settings and the trust teachers place in their institutions. This implies that the level of inclusivity in leadership significantly contributes to an optimistic shift of approximately 68% in educators' perspectives on institutional trust. Additionally, it is noteworthy that male teachers report significantly higher levels of organizational trust compared to their female colleagues. In summary, this research highlights the importance of considering the educational context when examining the correlation between organizational trust and inclusive leadership in educational institutions.